Inovaţia în ştiinţele sociale - Urse, Laureana (Calitatea Vieții, 2009)
Innovation in social sciences” completes the debate on the issue of social innovation as factor of the social-economic development. First, the innovation in science is analysed based on the book by T. Kuhn – Structure of the scientific revolutions; “the dynamic process by which scientific knowledge is acquired” is presented on the basis of the fundamental concepts of his book: paradigm, normal science, puzzles, anomaly, scientific crisis and revolution. The topic of innovation in social sciences is presented based on the book by M. Dogan and R. Phare „L’innovation dans les sciences sociales” and on the basis of several papers by Professor Cătălin Zamfir. M. Dogan and R. Pahre analyse how and where innovation in social sciences occurs, how the researcher innovates and what the innovation in social sciences can generate, but also considers that the science may also progress by successive inputs. The view points of Professor Cătălin Zamfir are oriented on two directions: 1) the characteristics of the social-humanist disciplines; 2) participation of sociology in the social change, focusing on the sociology of transition.